Impacts of fertilization management strategies on improved sorghums varieties in smallholder farming systems in Mali: Productivity and profitability differences - Akinseye, Folorunso M.; Zemadim, Birhanu; Ajeigbe, Hakeem A.; Diancoumba, Madina; Tabo, Ramadjita; Sanogo, Karamoko (Elsevier, 2023)
Sorghum is an important cereal crop cultivated by smallholder farmers of Mali, contributing significantly to their food demand and security. The study evaluated different fertilization stra- tegies that combined organic and inorganic fertilizer applications with three sorghum varieties. The experiments were conducted over three cropping seasons (2017–2019) in three sites (Bamako, Bougouni, and Koutiala respectively) within the Sudanian region of Mali. Our results showed a significant effect of season, variety, and fertilization strategies on grain and stalk yields. Grain yield increased by 8–40% in Koutiala, 11–53% in Bougouni, and 44–110% in Bamako while the average stalk yield was above 5000 kg ha 1 with fertilized treatment compared to unfertilized treatment in the three sites. Fadda performed the best variety, mean grain yield was 23% and 42% higher than that of Soumba and Tieble, respectively. Similarly, there was a progressive increase in grain yield with an increasing level of poultry manure (PM) from 0 to 150 g/hill and cattle manure (CM) from 0 to 100 g/hill. However, the application of 100 g/hill of CM and PM plus 3 g/ hill of Di-ammonium Phosphate (DAP) increased yield by 8% and 12% respectively compared to only CM or PM treatments. The results further revealed higher yield gain by 51% (Bamako), 57% (Koutiala), and 42% (Bougouni) for T10-[PM (100 g/hill) + Micro-D_DAP (3 g/hill)] equivalent to 73 kgNha 1 than others (T2-T9), but not proportionate to the highest value-cost ratio (VCR). Radar charts used to visualize sustainable intensification (SI) performance in the three domains (productivity, profitability, and environment) showed that the environmental variable has a direct influence on productivity, meanwhile profitability across the strategies ranged from low to moderate value across sites and different fertilizer strategies. Our study, therefore, recommends the use of multiple-choice fertilizer strategies includingT2-CM (50 g/hill)+PM(50 g/hill), T5-DAP- Micro-D (3 g/hill), T6-DAP41:46:00 and T9-PM(50 g/hill) alongside with improved sorghum varieties tested, for higher productivity and profitability across the region.